Review On Data Security Technology Based on Cloud Storage - Surender Kumar (AG Volumes, 2022)
Data security has become a major concern as cloud storage systems have been more widely used in a variety of complicated environments. It is possible that data may be incomplete due to node failures or other external intrusions, but it is also possible that cloud service providers actively hide or other circumstances make it difficult for the user to be aware of the change. Approaching the issue of security with more prudence is necessary There have been several techniques created to safeguard files and other information as computer and communication technologies have evolved. The term "computer network security" refers to a combination of tools, processes, rules, and solutions that are used to prevent and respond to assaults on a network. All of these ideas must be defined and learned in order to properly assess an organization’s security posture. Some of the methods and dangers to the network and computers are discussed in this document, along with possible programmes.